PENGARUH MARKET SHARE DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON EQUITY (Kasus pada PT Kalbe Farma Tbk) - Angga Gumilar; Asep Endri Mulyana (BanKu: Jurnal Perbankan dan Keuangan, 2022)
ABSTRACTThe purpose of this study was to determine and analyze Market Share, Total Assets Turnover, Return on Equity (ROE) and the magnitude of the influence of Market Share and Total Assets Turnover (TATO) on Return on Equity (ROE) at PT Kalbe Farma Tbk in 2010-2019. The research approach used in this study is a quantitative approach with an explanatory type of method. This study uses secondary data with purposive sampling analysis sampling technique. The statistical method used is multiple linear regression. Based on the results of the analysis at PT Kalbe Farma Tbk for the period 2010-2019 that the Market Share, Total Assets Turnover and Return On Equity fluctuated. The influence of Market Share and Total Assets Turnover on Return On Equity simultaneously is 57.4%. The results of the hypothesis test state that there is no significant effect of Market Share and Total Assets Turnover on Return On Equity. The effect of Market Share on Return On Equity partially results from the hypothesis that there is a significant effect of Market Share on Return On Equity. While the results of the hypothesis of the effect of Total Assets Turnover on Return On Equity partially the results of hypothesis testing state that there is no significant effect of Total Assets Turnover on Return On Equity at PT Kalbe Farma Tbk.Keywords: market share; total assets turnover; return on equity. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui dan menganalisis Market Share, Total Assets Turnover, Return on Equity (ROE) dan besarnya pengaruh Market Share dan Total Assets Turnover (TATO) terhadap Return on Equity (ROE) pada PT Kalbe Farma Tbk tahun 2010-2019.  Pendekatan penelitian yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan jenis metodenya explanatory. Penelitian ini menggunakan data sekunder dengan teknik sampling analisis purposive sampling. Metode statistik yang digunakan adalah regresi linier berganda. Berdasarkan hasil analisis pada PT Kalbe Farma Tbk periode 2010-2019 bahwa Market Share, Total Assets Turnover dan Return On Equity mengalami fluktuatif. Besar pengaruh Market Share dan Total Assets Turnover terhadap Return On Equity secara simultan adalah sebesar 57,4%. Hasil uji hipotesis menyatakan bahwa tidak terdapat pengaruh signifikan Market Share dan Total Assets Turnover terhadap Return On Equity. Secara parsial hasil hipotesis menyatakan terdapat pengaruh signifikan Market Share terhadap Return On Equity. Sedangkan Total Assets Turnover secara parsial tidak terdapat pengaruh signifikan terhadap Return On Equity pada PT Kalbe Farma Tbk.Kata Kunci: market share; total assets turnover; return on equity.